Culture :reinventing the social sciences - Smith, Mark J. (Rawat, 2019)
In the past three decades there has been a transformation in the ways that social science has been conducted. In order to understand what is happening, we have to explore the implications of a rethinking of the meaning of culture, from a hierarchical system of classification to a contested space. This introduction to the concept of culture examines the ways in which we approach social enquiry, and argues that cultural theory can help to overcome problems in disciplinary and interdisciplinary analysis.